Clinical features and presentation of cervicofacial infection: a Maxillofacial Trainee Research Collaborative (MTReC) study. Issue 4 (May 2021) - Henry, A.; Dawoud, B.; Kent, S.; McDonald, C.; Logan, G.; Hennedige, A.; Exely, R.; Regan, A.; Kulkarni, R.; Gilbert, K.; Basyuni, S.; Young, D.; et al.
Abstract: Cervicofacial infection (CFI) is a common presentation to the Oral and Maxillofacial (OMFS) department and accounts for significant emergency activity. The current study aims to understand the aetiology, management, and clinical features of patients hospitalised with CFI. Our study included all patients admitted for management of CFI from May to October 2017 at 25 OMFS units across 17 UK regions. Data were collected prospectively and included age, comorbidities, prior treatment received, markers of sepsis, and presenting clinical features. One thousand and two (1002) admissions were recorded; 546 (54.5%) were male. Median (range) age was 34 (1–94) years. The most common presenting complaints were trismus (46%) and dysphagia (27%). Airway compromise was present in 1.7% of cases. Odontogenic infection accounted for 822/1002 (82%) admissions. Of those with an infection of odontogenic origin, 453/822 (55.1%) had received previous treatment. Two-thirds of those who had received treatment were managed by antibiotics alone (300/453, 66.2%). Patients met criteria for sepsis in 437/1002 (43.6%) of CFI, and in 374/822 (45.5%) of odontogenic infections. This is the largest study worldwide of patients requiring inpatient management for CFI. Infection due to odontogenic origin is the most frequent reason for admission and nearly half do not seek treatment before presentation. Patients with CFI often present late in their disease and frequently meet criteria for sepsis, requiring timely and aggressive treatment to ensure optimum outcomes. Trismus is an emerging dominant feature with all the implications related to the anaesthetic management of these patients. Knowledge of these factors has implications for the referrer, triage, the emergency department, the anaesthetic team, and members of the OMFS team.